The Role of Motivation, Activeness, and Numeracy Skills on Grade X Vocational High School Students’ Mathematics Learning Achievement - Aulia, Syifa Rahma; Rejeki, Sri (Journal of Medives : Journal of Mathematics Education IKIP Veteran Semarang; Vol 7 No 2 (2023): Journal of Medives : Journal of Mathematics Education IKIP Veteran SemarangDO - 10.31331/medivesveteran.v7i2.2701, 2023)
This study aims to analyze and describe the contribution of learning motivation, learning activeness, and numeracy skills on vocational high school students' mathematics learning achievement. This quantitative research involves a population of grade X students at a private vocational high school in Surakarta, Central Java, Indonesia, Academic Year 2022/2023. With the quota sampling technique, 45 students were obtained as the research sample. The data-collecting method applied is questionnaires and tests. The data were analyzed using multiple linear regression tests with a significance level of 5% using SPSS software. The normality, linearity, multicollinearity, autocorrelation, and heteroscedasticity tests were performed as prerequisite analysis tests. Based on the results of data analysis, it can be concluded that: (1) There is a significant contribution of learning motivation to student learning outcomes with a partial determination coefficient of 14.77, (2) There is no significant contribution of active learning to student learning outcomes, with a partial determination coefficient of 3.21. (3) There is no significant contribution from numeracy skills to student learning outcomes, with a partial determination coefficient of 0.01, (4) there is a significant contribution of learning motivation, learning activeness, and numeracy skills on vocational high school students mathematics learning achievement with a simultaneous determination coefficient ( ) of 0.18. It means that the percentage of contribution given by learning motivation, learning activeness, and numeracy skills on vocational high school students mathematics learning achievement is 18%. In comparison, other factors outside this study influence the remaining 82%. Keywords : learning motivation, learning activeness, numeracy skills, and mathematics learning achievement .